Religion, Games, and Othering: An Intersectional Approach. - Trattner, Kathrin (Gamevironments, 2016)
Despite the fact that the medium is technologically capable of an infinite number of representations nowadays, video games still frequently resort to simplistic, ideologized and stereotypical portrayals of characters as well as virtual environments. Binary othering constructions of race, gender, national, cultural or religious identities are common modes of representation in any genre. I argue that in many instances religious identity as an excluding and marginalizing element only becomes visible in all its complexity when examined intersectionally, meaning in relation to other categories of difference. This article explores how religion can function as an element of othering in video game representations and how it appears as such in relation to other categories of difference. This is investigated by looking at the example of representations of Islam and the Middle East in contemporary military shooters, specifically in Medal of Honor: Warfighter (2012). Taking metaludic discourses into account (Ensslin 2012, 9), the article concludes with an examination of comments on YouTube-Walkthroughs to investigate whether the othering representations observed in the game are also perceived as such by gamers.